Development STEM E-Booklet Curug Winong Fern Plants as a Student Learning Resource - Febriyanto Febriyanto; Yustinus Ulung Anggraito (Bioeduca : Journal of Biology Education, 2023)
This study aims to determine the types of ferns in the Curug Winong and the results of the E-booklet product feasibility test from the research results. This research uses the Research and Development method with a size trap of 4 x 4 m. The results of the identification of ferns recorded 39 species of ferns which are divided into 17 families, 6 ordo, and 3 classes. The dominant percentage can be seen from the highest INP calculation, namely P. Biaurita and S. Ornate, while the exposed INP values are A. Evecta and G. Verrucosum. The index of plant diversity in Curug Winong is of moderate criteria. The results of the validation of material experts (77.78%), media (96.13%), teacher responses (91.67%), overlap test (83.66%), and student responses (83.90%). These results indicate that the E-booklet that was developed is suitable to be used as a learning resource.